Lifestyle and health of teachers of a public education institution - Renata Cristina da Penha Silveira; Isabely Karoline da Silva Ribeiro; Graziela Silveira Teixeira; Lidiane Naiara Teixeira; Paulo Henrique Alves Sousa (Universidade Federal de Santa Maria, 2017)
Aim: to identify the lifestyle and health of teachers of a public educational institution. Method: quantitative, descriptive, correlational study. The sample consisted of 82 professors of Biochemistry, Nursing, Pharmacy and Medicine. A semi-structured questionnaire was used to characterize the socio-demographic and work profile; Validated scale of the Fantastic Lifestyle. Results: 65.9% women, 74.4% doctors, 58.3% reported a very good lifestyle, 24.4% withdrawn due to illness; 68.2% of teachers with very good lifestyle did not use daily medication, while for those who used daily medication, the very good lifestyle dropped to 42.9%. Conclusion: it is necessary to emphasize the need to create public health policies that aim to promote health in the university environment and the production of new studies about health changes in teachers and their repercussions on the lifestyle.